APAKAH KEPRIBADIAN, KEKOSMOPOLITAN, DAN ORIENTASI NILAI MENENTUKAN KUALITAS HIDUP SUBJEKTIF KELUARGA? - Simanjuntak, Megawati; Sabrina, Olivia (Jurnal Ilmu Keluarga dan Konsumen, 2015)
Personality, cosmopolitanism, and value orientation can affect the life quality of families who lived in the city. The objective of the research was to analyze the effect of personality, cosmopolitanism, and value orientation on subjective life quality of family in Bogor City, West Java Province. This research used a cross sectional study design and involved 56 families. Data was collected by interview with wife using questionnaire. Furthermore, data was analyzed using Pearson’s correlation test and multiple linear regression. The result showed that family value, societal consciousness, and value orientation was correlated significantly with subjective life quality of family and also with two dimension of subjective life quality of family. Value orientation of traditionalism correlated significantly with subjective life quality of family and also with subjective life quality personal. Societal consciousness had an effect on subjective life quality of family and the dimensions of subjective life quality of family, subjective life quality social.